Características epidemiológicas e análise temporal de sífilis congênita na região norte do Brasil de 2010 a 2019 - SANTOS, Fabio Conceição dos (Universidade Federal do Pará, 2023)
Introduction: Sexually transmitted infections (STIs) are considered a public health problem, with a direct impact on reproductive and child health, causing infertility and complications in pregnancy and childbirth, in addition to causing fetal death and health problems for children permanent. Among the STIs, syphilis is one of the most frequent, being exclusive to humans, and when vertical transmission occurs, it is called congenital syphilis. Worldwide efforts are used to eliminate Congenital Syphilis, however, its incidence is still high in several countries around the world, including Brazil. Objective: To evaluate the epidemiology and temporal trend of Congenital Syphilis in the North region of Brazil from 2010 to 2019. Materials and Method: This is an epidemiologicaldescriptive, retrospective research with a quantitative approach, which analyzed the epidemiological and temporal profile of cases of Congenital Syphilis in the Northern Region of Brazil from 2010 to 2019, through data recorded in SINAN AND SINASC. A descriptive analysis of the sociodemographic data was carried out, followed by a temporal analysis, through the calculation of the incidence of the regression model by inflection points (Joinpoint Regression Analysis), which allows knowing the annual percentage change (APV) and that of the entire period, called average annual percentage change (VPAM). For each trend detected, the 95% confidence interval was considered. The significance level adopted was 5%. Results: 14,434 cases of congenital syphilis were registered in the North Region, with the state of Pará being the most notified, followed by Amazonas and Tocantins. The data signaled the maternal characteristics, showing that most were of reproductive age, followed by those with a migratory period to adulthood. Most did not complete elementary and high school, with a phenotypic predominance of brown, followed by white. Still, most of the diagnosis of gestational syphilis happened in prenatal care, with them performing followup in 79.54% of cases, and partners in treatment in only 34.68%, with recent congenital syphilis as the most diagnosed in 99, 73% from birth to incomplete 23 months. There was significance for the average annual increasing incidence rates in several states and capitals in the region. All capitals showed a yeartoyear growth trend, with fluctuating periods, as seen in the capitals Macapá and Boa Vista between 2014 and 2015. The capital Belém showed a peak incidence of congenital syphilis cases between 2015 and 2016 (highest incidence rate between years). Other capitals such as Manaus and Palmas had an explosion of cases in 2018, with 19.8 and 17.6 for every thousand live births. Conclusion: In this study there was a limitation in terms of time for an investigation with greater accuracy, which should include other epidemiological and local data, and in regions with a higher incidence of this pathology. Therefore, it is necessary to carry out other studies on SC that work with spatial analysis in its various regions, contributing to the improvement of maternal and child health indicators in the region under study.